The study on freshwater fish biodiversity of ukkadam (periyakulam) and valankulam lake from coimbatore district, tamil nadu, india - T, Dharani; G, Ajith; S, Rajeshkumar (Kongunadu Research Journal, 2020)
Wetlands of India preserve a rich variety of fish species. Globally wetlands as well as fauna and flora diversity are affected due to increase in anthropogenic activities. The present investigation deals with the fish bio-diversity of selected major wetlands Periyakulam famously called Ukkadam Lake, Singanallur Lake and Sulur Lake of Coimbatore district fed by Noyyal River. Due to improper management of these lentic wetlands water bodies around Coimbatore district by using certain manures, insecticides in agricultural practices in and around these selected areas has polluted the land and these fresh waters creating hazards for major vertebrate fishes which are rich source of food and nutrition, an important and delicious food of man. The results of the present investigation reveals the occurrence of 19 fish species belonging to 5 order, 8 families 18 species recorded from the Ukkadam wetland followed by Singanallur wetland with 5 different orders 7 different families and 14 species. Ichthyofaunal diversity of Sulur wetland compressed of 6 families with 14 species. The order Cypriniformes was found dominant followed by Perciformes, Ophicephalidae, Siluriformes and Cyprinodontiformes species in Ukkadam and Singanallur wetland lakes while in Sulur it was recorded as Cyprinidae > Cichlida > Ophiocephalidae > Anabantidae > Bagridae > Heteropneustidae. This study on the freshwater fish species diversity of these wetlands would help in explore the fish fauna status and estimate the factors that may need rectification for fish conservation and management.